Listen-Read-Discuss (L-R-D) Strategy to Foster Students' Reading Comprehension - Kamarudin (The Center for Language Development, Mataram State Islamic University., 2022)
The goal of this study was to see if the Listen-Read-Discuss (LRD) technique improves students' reading comprehension. The study was conducted in a classroom setting. The study focused on second-grade pupils in SMAN 4 Mataram, West Nusa Tenggara. The information was gathered using both quantitative and qualitative methods. The results of the pre-test and post-test from the reading test provided quantitative data. Meanwhile, qualitative data was gathered using observation sheets about the activities of students and teachers. The test and observation sheet were the instruments utilized by the researcher. The research found that using the Listen-Read-Discuss technique improves students' reading comprehension in descriptive texts. The mean score of pupils from pre-test, post-test one, and post-test two shows an improvement. Pre-test mean score was 64.46 (50%); eight students passed the minimum passing grade; post-test one mean score was 75.35 (67%); twelve students achieved the minimum passing grade; and post-test two mean score was 82.14 (89%); twenty-five students got the minimum passing grade (KKM).